Beyond the willing suspension of disbelief : poetic faith from Coleridge to Tolkien - Tomko, Michael, 1975- (New directions in religion and literature., 2016)
"Samuel Taylor Coleridge's conception of "the willing suspension of disbelief" marks a pivotal moment in the history of literary theory. Returning to Coleridge's thought and Shakespeare criticism to reconstruct this idea as a form of "poetic faith", Michael Tomko here lays the foundations of a new theologically oriented mode of literary criticism. Bringing Coleridge into dialogue with thinkers ranging from Augustine to Josef Pieper, contemporary critics such as Stephen Greenblatt and Terry Eagleton as well as writers like J.R.R. Tolkien and Wendell Berry, Beyond the Willing Suspension of Disbelief offers a method of reading for post-secular literary criticism that is not only historically and politically aware but also deeply engaged with aesthetic form."--Bloomsbury Publishing